2018
DOI: 10.1101/393710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The core genome m5C methyltransferase JHP1050 (M.Hpy99III) plays an important role in orchestrating gene expression in Helicobacter pylori

Abstract: 6Helicobacter pylori encodes a large number of Restriction-Modification (R-M) systems despite its 1 7 small genome. R-M systems have been described as "primitive immune systems" in bacteria, but the 1 8 role of methylation in bacterial gene regulation and other processes is increasingly accepted. Every H.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…DNA methylation can have a profound effect on gene transcription, both up-regulating and down-regulating transcript levels in bacteria ( 39–41 ). To study the potential transcriptional effects of the different methylation patterns in the locked mutants, we performed RNA-Seq analysis.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation can have a profound effect on gene transcription, both up-regulating and down-regulating transcript levels in bacteria ( 39–41 ). To study the potential transcriptional effects of the different methylation patterns in the locked mutants, we performed RNA-Seq analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search mostly yielded basic research studies investigating a broad spectrum of fundamental mechanism in H. pylori like the presence of genes associated with bacterial virulence[99-104] and biofilm formation[105,106], the characterization of methylases[107], nudix hydrolases[108], restriction-modification (R-M) systems[109], exo- and endo-ribonucleases[110] ; and the transcriptional response of H. pylori to exposition to different salt concentrations[111], different pH conditions[112], heat shock[113] and chemical agents like bismuth[114] and nickel[115]. Most of these studies initially depleted ribosomal RNA, either using RiboZero eukaryotic rRNA depletion treatment (Epicentre, Illumina)[112,113,116] or a rRNA modified capture hybridization approach[110], and performed sequencing on an Illumina platform (Illumina, United States).…”
Section: Next Generation Sequencing and Helicobacter Pylorimentioning
confidence: 99%
“…HPG27_1233, called JHP1050 in H. pylori J99, was recently demonstrated to affect the transcription of multiple genes, adherence to host cell, natural competence and bacterial cells shape (Estibariz, Overmann et al 2019). Here we demonstrated that HPG27_1233 also affects biofilm growth and its inactivation results in a significant decrease in biofilm formation of H. pylori G27.…”
Section: Genes Essential For Biofilm Formationmentioning
confidence: 99%